The Investigation of Factors Affecting the Gait of the Patients Suffering From Multiple Sclerosis - Amin Mahdizadeh; Somayeh Lokzadeh; Azadeh Riyahi; Seyed Ali Hosseini; Nasrin Jalili (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Multiple Sclerosis (MS) is a chronic inflammatory, demyelinating, and neurodegenerative disorder of the Central Nervous System (CNS) and it is also the most common cause of non-traumatic neurological disability in young adults. MS in women, especially young women, is about 1.5 to 3 times more common than men all over the world. About 2.5 million people worldwide are suffering from MS. The destruction of myelin in certain areas exhibits certain signs and symptoms. Balance disorders are particularly problematic because they are associated with difficulty in moving from one position to another, sustaining an upright posture, and performing functional activities such as walking and turning, all of which predisposes people with MS to the loss of equilibrium and falls. Isfahan City in Iran suffers from a high prevalence of MS that put it amongst the regions with the highest prevalence of MS in Asia and Oceania. This study aimed to use the holistic approaches of occupational therapy to investigate the physical and cognitive factors (attention, cognition and muscle strength of lower extremities) that affect the gait of MS patients in the city of Isfahan, Iran. Materials & Methods The present study was a descriptive-correlational one and convenience sampling method was used to recruit the samples. The study population consisted of all patients with MS in Isfahan City in August 2017. A group of 70 patients (24 males and 46 females with the Mean±SD age of 32.20±7.55 y) met the inclusion-exclusion criteria and were enrolled in the study. To be eligible for the study, the patients had to meet the following inclusion criteria: having a neurologist-confirmed diagnosis of MS with MRI scan, being able to read and write, and walk at least 100 m independently. We excluded patients with cognitive impairments that might hinder understanding of the tasks to be accomplished, those with any comorbid neurologic condition other than MS, and those who are unwilling to collaborate with the research process. After providing sufficient information about the research process and getting informed consent of the patients, the questionnaires and tests were provided to the participants to be completed. The study tools were the Mini-Mental Status Examination (MMSE), 10 m Walking Test (10 MWT), Timed Up and Go test (TUG), Sit to Stand test, and Stroop test. For data analysis, the Pearson correlation coefficient and multiple regression analysis were performed in SPSS version 16. Results In this study, 70 patients suffering from MS participated. The results showed a significant negative correlation between the scores of walking speed test (10 m walking) and the scores of the functional strength of the lower extremities muscles (P<0.001) and attention (P=0.01). There is also a significant correlation between muscle strength of lower extremity and balance (P=0.01). Regression analysis shows that the muscle strength of lower extremities has the highest contributions in predicting the speed of walking in patients with MS.  Conclusion According to the study findings, among the physical and cognitive factors affecting gait and balance such as muscle strength of lower extremity or cognition and attention, the muscle strength of lower extremity is the most important factor affecting the balance and speed of walking in patients with MS that still can walk. In the process of rehabilitation, especially in occupational therapy, special attention must be paid to a muscle strengthening program for the lower extremities of patients suffering from MS.